euroargodev/VirtualFleet: v0.3.0 EARISE release - Guillaume Maze; Kevin Balem (Zenodo, 2023)
VirtualFleet is a python library dedicated to compute and analyse trajectory simulations of virtual Argo floats. The optimisation of the Argo array is quite complex to determine in specific regions, where the local ocean dynamic shifts away from standard large scale open ocean. These regions are typically the Boundary Currents where turbulence is more significant than anywhere else, and Polar regions where floats can temporarily evolve under sea-ice. Furthermore, with the development of Argo float recovery initiatives, it becomes more crucial than ever to be able to predict float trajectories with mission parameters that can be modified on-demand remotely. VirtualFleet aims to help the Argo program to optimise floats deployment and programming. To do so, the VirtualFleet software provides a user-friendly, high-level, collection of Python modules and functions to make it easy to simulate . The general principle is to customise the behavior of particles in a Lagrangian simulation framework ( ) using output from ocean circulation models.